2015
DOI: 10.1002/pts.2185
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Packaging Development for Fresh Food Supply Chains

Abstract: The fresh food industry is increasingly more interested in developing efficient and innovative solutions to guarantee quality and distribution sustainability; one of the main factors that influences such crucial aspects is packaging. This paper aims to perform a critical analysis of two existing packaging solutions, i.e. corrugated fibreboard boxes and re‐usable plastic containers, from both the economic and the environmental perspective, to highlight the main weaknesses. It then proposes two alternative packa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The results obtained in this case study show the viability of a win-win relationship that several researchers (Atilgan & Azapagic, 2016;Battini, Calzavara, Persona & Sgarbossa, 2016;Carter & Rogers, 2008;Cordero, 2013;Garza-Reyes, Villarreal, Kumar & Molina-Ruiz, 2016) have found in the past. According to this approach, adopting environmentally sustainable policies may have a positive impact on cost reduction.…”
Section: Discussion and Further Researchsupporting
confidence: 69%
See 1 more Smart Citation
“…The results obtained in this case study show the viability of a win-win relationship that several researchers (Atilgan & Azapagic, 2016;Battini, Calzavara, Persona & Sgarbossa, 2016;Carter & Rogers, 2008;Cordero, 2013;Garza-Reyes, Villarreal, Kumar & Molina-Ruiz, 2016) have found in the past. According to this approach, adopting environmentally sustainable policies may have a positive impact on cost reduction.…”
Section: Discussion and Further Researchsupporting
confidence: 69%
“…Despite the notoriety of the win-win relationship in this case study, it is noteworthy that results may vary significantly depending on the values of the input data. This is critical when developing the packaging strategy of a company (Battini et al, 2016). For example, in the case analyzed by the authors, the corrugated cardboard box is clearly the best alternative in all cases, even when different scenarios are considered.…”
Section: Discussion and Further Researchmentioning
confidence: 96%
“…A study comparing cardboard boxes and reusable plastic containers concluded that cardboard is a better packaging option (both economically and environmentally) for short food supply chains [193]. On the contrary, a similar study conducted in Emilia-Romagna, Italy, concluded that reusable plastic containers will reduce environmental impact [194].…”
Section: Efficient Warehousing Policiesmentioning
confidence: 99%
“…Eighty percent of customer purchasing decisions for foodstuffs are made based on the packaging [1]. It is estimated that up to 50% of food is wasted in developing countries before it reaches retailers compared with 3% in developed countries, and packaging is thought to play a large part in this waste [1,2]. Packaging reduces damage in the supply chain and increases the shelf-life of products.…”
Section: Introductionmentioning
confidence: 99%